Design of an Energy System Based on Photovoltaic Thermal Collectors in the South of Algeria - Touafek, K.; Khelifa, A.; Adouane, M.; Haloui, H. (Journal of Renewable Energy, 2014)
The objective of this work is the design of a new energy system where the energy source will be provided by solar photovoltaic thermal (PV/T) hybrid collectors. This system will be applied to a habitation in the region of Ghardaïa in the south of Algeria. The cold water reaches the thermal storage tank and then will be heated by the hybrid collector. The hot water will be used directly as sanitary water. The electric power produced by the hybrid collector will be used to charge the battery and will be delivered to the load (electrical appliances, lamps, etc.). Two types of loads are considered: a DC load and the other alternating current. The fans located adjacent to the radiators supplied with hot water will provide warm air to the house in winter.